Effect of Gamma Irradiation and Selection with Fungus Filtrate (Rhizoctonia solani Kuhn) on the in Vitro Culture of Common Bean (Phaseolus vulgaris) - Solís Ramos, Laura Yesenia (2015)
The present investigation was undertaken to study the effect of gamma irradiation (dose from 10 to 100 Gy) and in vitro selection with fungus filtrate as selecting agent (concentration from 20% to 100%) on the susceptibility of the common bean to Rhizoctonia solani. The best results were found with a dose of 20 Gy or a concentration of 20% of fungus filtrate applied separately. These conditions were used to evaluate the combined effect of both approaches in a second experiment. The combined effect of irradiation and then selection adversely affected growth (height and roots) and survival of the in vitro plants. It may not be necessary to combine the variation generated by irradiation with the selection technique. For future assays we propose the application of: 1) gamma radiation, thereby inducing not only mutants with pathogen resistance, but also with other agronomic traits of interest. Later in the subculture MV4 potential fungus-resistant mutants will be evaluated in the field; or 2) selection pressure using fungus filtrate during three subcultures, which may be sufficient to induce the variation necessary to obtain in vitro plants resistant to fungus.